Modulators of very low voriconazole concentrations in routine therapeutic drug monitoring - Hassan, Arwa; Burhenne, Jürgen; Riedel, Klaus-Dieter; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E.; Czock, David (Therapeutic drug monitoring, 2011)
Very low voriconazole concentrations are commonly observed during therapeutic drug monitoring. Possible mechanisms include inappropriate dose selection, rapid metabolism (as a result of genetic polymorphisms or enzyme induction), and also nonadherence. We aimed to develop a method to distinguish between rapid metabolism of and nonadherence to voriconazole by quantification of voriconazole metabolites. In addition, the relevance of common genetic polymorphisms of CYP2C19 was assessed. In a retrospective study, samples with voriconazole concentrations 0.2 μg/mL or less in routine therapeutic drug monitoring (as quantified by high-performance liquid chromatography) were evaluated. Voriconazole and its N-oxide metabolite were quantified in residual blood using a highly sensitive liquid chromatography-tandem mass spectroscopy method (lower limit of quantitation = 0.03 μg/mL). Genetic polymorphisms of CYP2C19 were determined by real-time polymerase chain reaction using the hybridization probe format and the polymerase chain reaction-random fragment length polymorphism format. A total of 747 routine therapeutic drug monitoring plasma/blood samples of 335 patients treated with systemic voriconazole were analyzed and in 18.7% of all samples, voriconazole concentrations 0.2 μg/mL or less were found. In 32 samples (30 patients) with adequate dosage and timing of blood withdrawal, nonadherence was strongly suspected in seven patients because voriconazole-N-oxide concentrations were below 0.03 μg/mL, which was not observed in a reference group of 51 healthy volunteers with controlled drug intake. In 10 patients, of whom EDTA blood was available, the ultrarapid metabolizer genotype (CYP2C19*1\*17, CYP2C19*17\*17) was found in 80% and its prevalence was significantly higher as compared to a reference group (P = 0.02). In conclusion, quantification of voriconazole-N-oxide allowed for detection of suspected nonadherence in one of four patients with very low voriconazole concentrations. In the remaining patients, ultrarapid metabolism resulting from the CYP2C19*17 polymorphism appears to play a major role. Thus, in the case of voriconazole therapy failure, both nonadherence and genetic factors have to be considered.
Gesehen am 31.08.2022